2015
DOI: 10.3390/microarrays4020245
|View full text |Cite
|
Sign up to set email alerts
|

Re-Punching Tissue Microarrays Is Possible: Why Can This Be Useful and How to Do It

Abstract: Tissue microarray (TMA) methodology allows the concomitant analysis of hundreds of tissue specimens arrayed in the same manner on a recipient block. Subsequently, all samples can be processed under identical conditions, such as antigen retrieval procedure, reagent concentrations, incubation times with antibodies/probes, and escaping the inter-assays variability. Therefore, the use of TMA has revolutionized histopathology translational research projects and has become a tool very often used for putative biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Indeed, research has shown that punches taken from donor blocks can be re-punched directly into tubes and used for molecular analysis using PCR-based approaches. By doing so, cytopathologists could have the means not only to compare IHC with molecular data in large-scale analyses, but also to investigate rare subpopulations identified during preliminary cbTMA analysis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has shown that punches taken from donor blocks can be re-punched directly into tubes and used for molecular analysis using PCR-based approaches. By doing so, cytopathologists could have the means not only to compare IHC with molecular data in large-scale analyses, but also to investigate rare subpopulations identified during preliminary cbTMA analysis [20,21].…”
Section: Discussionmentioning
confidence: 99%